On A solution to the ecological problem: reconstructing individual behavior from aggregate data, by Gary King. (Annals of the Association of American Geographers, 2000)
A special review section on Gary King's A Solution to the Ecological Problem: Reconstructing Individual Behavior from Aggregate Data.